Silver Sulfadiazine Eradicates Antibiotic-Tolerant Staphylococcus aureus and Pseudomonas aeruginosa Biofilms in Patients with Infected Diabetic Foot Ulcers - Di Domenico, Enea Gino (J Clin Med, 2020)
Infections are among the most frequent and challenging events in diabetic foot ulcers (DFUs). Pathogenic bacteria growing in biofilms within host tissue are highly tolerant to environmental and chemical agents, including antibiotics. The present study was aimed at assessing the use of silver sulfadiazine (SSD) for wound healing and infection control in 16 patients with DFUs harboring biofilm-growing Staphylococcus aureus and Pseudomonas aeruginosa. All patients received a treatment based on a dressing protocol including disinfection, cleansing, application of SSD, and application of nonadherent gauze, followed by sterile gauze and tibio-breech bandage, in preparation for toilet surgery after 30 days of treatment. Clinical parameters were analyzed by the T.I.M.E. classification system. In addition, the activity of SSD against biofilm-growing S. aureus and P. aeruginosa isolates was assessed in vitro. A total of 16 patients with S. aureus and P. aeruginosa infected DFUs were included in the study. Clinical data showed a statistically significant (p < 0.002) improvement of patients’ DFUs after 30 days of treatment with SSD with significant amelioration of all the parameters analyzed. Notably, after 30 days of treatment, resolution of infection was observed in all DFUs. In vitro analysis showed that both S. aureus and P. aeruginosa isolates developed complex and highly structured biofilms. Antibiotic susceptibility profiles indicated that biofilm cultures were significantly (p ≤ 0.002) more tolerant to all tested antimicrobials than their planktonic counterparts. However, SSD was found to be effective against fully developed biofilms of both S. aureus and P. aeruginosa at concentrations below those normally used in clinical preparations (10 mg/mL). These results strongly suggest that the topical administration of SSD may represent an effective alternative to conventional antibiotics for the successful treatment of DFUs infected by biofilm-growing S. aureus and P. aeruginosa.